Moral Education Values in the Novel of Bumi Cinta by Habiburrahman El-Shirazy - Sa'diyah, Arfina; Robingun Suyud El Syam; Noor Aziz; Ashief El Qorny; Aprezo Pardodi Maba (KURAS Institute, 2023)
This article aimed to know the values of moral education in the novel Bumi Cinta by Habiburrahman El Shirazy and the urgency of moral education values in the novel Bumi Cinta by Habiburrahman El Shirazy towards learning in the current era. This study uses a qualitative research approach. This research is included in library research or library research. The data collection technique for this research uses documentation techniques, which means books, articles, journals, and scientific works related to this research. The data analysis technique uses content analysis techniques to analyze and process the message. The results of this study can conclude that there are four values of moral education, namely: first moral values towards Allah, including prayer, repentance, dhikr, tawakkal, gratitude, and fear ‘khauf’. Second, moral values towards oneself include maintaining self-purity, being patient, lowering one's gaze, being brave, and being disciplined. Third, family moral values, including filial piety to parents ‘birrul walidain’, Fourth, societal values, including mutual help, religious tolerance, humility, and amar ma'ruf nahi munkar.